Reduced Phrenic Motoneuron Recruitment during Sustained Inspiratory Threshold Loading Compared to Single-Breath Loading: A Twitch Interpolation Study - Raux, Mathieu; Demoule, Alexandre; Redolfi, Stefania; Morelot-Panzini, Capucine; Similowski, Thomas (Frontiers in Physiology, 2016)
In humans, inspiratory constraints engage cortical networks involving the supplementary motor area. Functional magnetic resonance imaging (fMRI) shows that the spread and intensity of the corresponding respiratory-related cortical activation dramatically decrease when a discrete load becomes sustained. This has been interpreted as reflecting motor cortical reorganisation and automatisation, but could proceed from sensory and/or affective habituation. To corroborate the existence of motor reorganisation between single-breath and sustained inspiratory loading (namely changes in motor neurones recruitment), we conducted a diaphragm twitch interpolation study based on the hypothesis that motor reorganisation should result in changes in the twitch interpolation slope. Fourteen healthy subjects (age: 21 – 40 years) were studied. Bilateral phrenic stimulation was delivered at rest, upon prepared and targeted voluntary inspiratory efforts ("vol"), upon unprepared inspiratory efforts against a single-breath inspiratory threshold load ("single-breath"), and upon sustained inspiratory efforts against the same type of load ("continuous"). The slope of the relationship between diaphragm twitch transdiaphragmatic pressure and the underlying transdiaphragmatic pressure was –1.1 ± 0.2 during "vol", –1.5 ± 0.7 during "single-breath", and -0.6 ± 0.4 during "continuous" (all slopes expressed in percent of baseline.percent of baseline-1) all comparisons significant at the 5% level). The contribution of the diaphragm to inspiration, as assessed by the gastric pressure to transdiaphragmatic pressure ratio, was 31 ± 17 % during "vol", 22 ± 16 % during "single-breath" (p=0.13), and 19 ± 9 % during "continuous" (p = 0.0015 vs. "vol"). This study shows that the relationship between the amplitude of the transdiaphragmatic pressure produced by a diaphragm twitch and its counterpart produced by the underlying diaphragm contraction is not unequivocal. If twitch interpolation is interpreted as reflecting motoneuron recruitment, this study supports motor reorganisation compatible with "diaphragm sparing" when an inspiratory threshold load becomes sustained